Critical hydrogen concentration for crack propagation in a CrMo steel: Targeted experiments for accurate numerical modelling. (1st October 2022) - Peral, Luis Borja; Fernández-Pariente, Inés; Colombo, Chiara
Graphical abstract: Highlights: Fracture toughness tests of a CrMo steel experiencing HEDE mechanism are simulated. Dislocations act as reversible trapping sites for hydrogen atoms. Embrittlement depends on the critical H concentration at the tip. Targeted experiments are crucial to simulate accurately this H concentration. Critical H reduces of −21% with two orders of magnitude decrease in test speed. Abstract: This study focuses on CrMo steel experiencing decohesion mechanism in presence of hydrogen. A tailored experimental characterization is performed with tensile, permeation and toughness experimental tests to obtain all the inputs for the numerical simulations of a propagating crack in a C(T) specimen. The used finite element framework is based on the cohesive zone modelling. The aim of the numerical model and of the work is the identification of a critical hydrogen concentration inducing crack tip propagation. Given the tailored inputs, these models accurately estimate the hydrogen concentrations in the lattice and the reversible traps, and follow their redistribution along the ligament during the time. From the obtained results, we could quantify that a decrease of two orders of magnitude in the test speed reduces the critical hydrogen concentration at the crack tip, necessary to activate the failure of the first cohesive element and therefore the propagation, from 0.994 to 0.784 wppm, that is −21%.